2009
DOI: 10.1016/j.virusres.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between infectious pancreatic necrosis virus (IPNV) and the IFN system: IFN signaling is inhibited by IPNV infection

Abstract: Infectious pancreatic necrosis virus (IPNV) is a major pathogen in the aquaculture industry worldwide. Factors contributing to IPNV pathogenicity are yet poorly understood. Indications of IPNV being able to evade or counteract innate host defense come from its lack of ability to induce strong type I interferon (IFN) responses in cell culture. We show here that addition of salmon rIFN-alpha1 to cells prior to IPNV infection halts the viral protein synthesis and prevents processing of pVP2 into mature VP2. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 35 publications
8
38
1
Order By: Relevance
“…Although in our study Mx-1 after day 7 was not able to exploit the biological function reported in CHSE-214 cells (Larsen, Rokenes, & Robertsen, 2004) and in vivo studies (Saint-Jean, & Pérez-Prieto, 2007). Skjesol et al (2009) have referred and pointed to VP4 and VP5 proteins like IPNV virulence factors, however is unknown until now. Although, Dobos (1995) found that IPNV replicates in the cytoplasm, and virus and proteins never enter the cell nucleus, we believe that this issue needs to get the focus.…”
Section: Discussioncontrasting
confidence: 56%
“…Although in our study Mx-1 after day 7 was not able to exploit the biological function reported in CHSE-214 cells (Larsen, Rokenes, & Robertsen, 2004) and in vivo studies (Saint-Jean, & Pérez-Prieto, 2007). Skjesol et al (2009) have referred and pointed to VP4 and VP5 proteins like IPNV virulence factors, however is unknown until now. Although, Dobos (1995) found that IPNV replicates in the cytoplasm, and virus and proteins never enter the cell nucleus, we believe that this issue needs to get the focus.…”
Section: Discussioncontrasting
confidence: 56%
“…IPNV itself does not induce IFN or Mx in TO or CHSE cells (20,21,42). In fact, proteins encoded by IPNV inhibit both activation of the IFNa1 promoter (unpublished results) and inhibit IFNa1-mediated signaling (49). Anti-IFNa1 also seemed to reduce the antiviral activity of IFN-␥ against SAV3, but here the mechanism is less clear since the virus itself is known to induce IFN.…”
Section: Discussionmentioning
confidence: 89%
“…Further, in light of recent publications showing that IPNV has the ability to reduce/block IFNα-induced responses in vitro [24], [25] we examined replication differences between TA and TT strains under IFNα-1 influence. We therefore performed an in vitro study with the purpose to explore the possibility that TA and TT strains differ in their sensitivity to IFN-α1 induced antiviral responses.…”
Section: Resultsmentioning
confidence: 99%